Young Finnish Unemployed Men's Experiences of Having Participated in a Specific Active Labor Market Program. (September 2017) - Björklund, Ove; Häggström, Elisabeth; Nyström, Lisbet
The purpose of the present study was to describe young Finnish unemployed men's experiences of having participated in a specific active labor market program, intended to fight unemployment and offered at a resource center. Fifteen young unemployed Finnish men in the age range 18 to 27 years were interviewed face-to-face. Purposive sampling was used to increase the variation among informants. The interview texts were analyzed using both manifest and latent qualitative content analysis. The present results reported that the young men felt that they, thanks to the program at the resource center, had acquired daily routines and could ultimately believe in the future. The young men described how they now had a structure, economic support, and that they could return to their daily life. The informants also described how they could see new possibilities and believe in oneself. There is a lack of empirical studies assessing the possible impact of active labor market programs on the unemployed based on participants' own experiences. Further research is needed to describe and elucidate in more detail the effects of targeted support measures and the needs of unemployed men of different ages and living in different contexts.